2021
DOI: 10.3390/pharmaceutics13101633
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Improving Dermal Permeation on the Efficacy and Targeting of Liposome Nanoparticles as a Potential Treatment for Breast Cancer

Abstract: Breast cancer is the most frequent malignancy in women. This work focuses on developing deformable liposomes as a potential carrier for breast cancer treatment and studying the impact of improving dermal permeation on the efficacy and targeting of liposomes. Raloxifene (RXF), an oestrogen antagonist, was used as a model drug. Using Box–Behnken design, different formulations of RXF-loaded deformable liposome (RLDL) were prepared using different propylene glycol, phospholipid and cholesterol concentrations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 43 publications
(86 reference statements)
1
28
0
Order By: Relevance
“…Moreover, it was observed that X 2 had a positive effect on ZP which may be owed to that the cholesterol molecule contains a hydroxyl group in its structure. Besides, it is a rigid molecule that aids in improving the stability and rigidity of the lipid bilayer [ 23 ]. Similar findings were reported by Salem et al (2021) who found that the negative charges in vesicles were increased when cholesterol was increased [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was observed that X 2 had a positive effect on ZP which may be owed to that the cholesterol molecule contains a hydroxyl group in its structure. Besides, it is a rigid molecule that aids in improving the stability and rigidity of the lipid bilayer [ 23 ]. Similar findings were reported by Salem et al (2021) who found that the negative charges in vesicles were increased when cholesterol was increased [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…A sample of the VLI and VLL formulations was deposited onto a carbon-coated copper grid and visualized by Transmission Electron Microscopy (TEM, Carl Zeiss, Oberkochen, Germany) at suitable magnifications [13].…”
Section: Transmission Electron Microscopy (Tem) Measurementmentioning
confidence: 99%
“…They can enhance the pharmacokinetics, selectivity, and efficacy of drugs while lowering their toxicity [4,11,12]. Liposomes were first described as nanoparticles Pharmaceuticals 2022, 15, 126 2 of 14 for transdermal use [11,13]. Phospholipids and cholesterol are the main components of liposomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this, a prospective MTX-GNPs formula has been prepared to encapsulate MTX, in order to achieve better drug permeation and bioavailability. In addition, new topically applied methodologies are being investigated [ 18 ]. In general, linking MTX to GNPs aids in more effective and selective uptake, a property distinct to nanocarriers, which improves therapeutic potential and lowers effective doses [ 19 ].…”
Section: Discussionmentioning
confidence: 99%